ANALISIS PENGARUH KEADILAN ORGANISASI, KEPUASAN KERJA DAN KOMITMEN ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR PEGAWAI SEKRETARIAT DAERAH KABUPATEN LAMPUNG TENGAH - Siswanto Siswanto; Marzuki Noor; Suharto Suharto (SIMPLEX: Journal of Economic Management, 2021)
The purpose of this study is to examine and analyze the influence of organizational justice, job satisfaction and organizational commitment to the organizational citizenship behavior of the Regional Secretariat of Central Lampung Regency employees. Respondents in this study were 28 employees of the Regional Secretariat of Central Lampung Regency. Data analysis in this study used quantitative analysis, namely by using multiple linear regression as a data analysis technique. The results of the study There is an effect of Organizational Justice on Organizational citizenship behavior of Regional Secretariat employees of Central Lampung Regency. There is an influence of Job Satisfaction on Organizational Citizenship Behavior of Regional Secretariat Employees in Central Lampung Regency. Organizational Justice, Job Satisfaction and Organizational Commitment to Organizational Citizenship Behavior of Regional Secretariat Employees in Central Lampung Regency. The magnitude of the Influence of Organizational Justice, Job Satisfaction and Organizational Commitment on Organizational Citizenship Behavior of Regional Secretariat Employees of Central Lampung Regency is 55.1%, while the rest is 44, 9% is influenced by other factors outside the model included in this study.